PENGARUH KOMIK PINTAR BELAJAR TRANSFUSI DARAH TERHADAP TINGKAT PENGETAHUAN PEMBERIAN TRANSFUSI DARAH DAN GAMBARAN MOTIVASI BELAJAR - Djoni, Arianto Arif; Rahajeng, Indah Mei; Saputra, I Kadek (Coping: Community of Publishing in Nursing; Vol 9 No 3 (2021): Juni 2021DO - 10.24843/coping.2021.v09.i03.p15, 2021)
Learning motivation may support students in learning can increase their knowledge. The skills to administer safe blood transfusions are essential for nursing students, thus for mastering the skill students need to be supportive with an effective learning tools. This study aims to determine the effect of smart comics for learning blood transfusion (KOPI BETA) on the level of knowledge in administering blood transfusions and a description of the learning motivation among nursing students at Nursing Study Program of the Faculty of Medicine Udayana University. This study used pre-experimental with a one-group pretest-posttest design. This research employed 61 nursing students class 2018 that selected by using total sampling technique. The intervention included the participants studied the KOPI BETA for a week. A questionnaire was used for data collection regarding the level of knowledge and learning motivation. The Wilcoxon test was performed for a bivariate analysis with a confidence level of 95% (? = 0.05). The findings showed that there was difference of the level of knowledge in administering blood transfusions before and after the intervention (p<0,0001; ? = 0,05). It shows that there is an effect of KOPI BETA on the level of knowledge regarding blood transfusions administration to the participants. The researchers recommend the nursing students to utilize this learning comic as learning media.